PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI MAN 2 MODEL PEKANBARU - Yanti, Remi Hasfita; Kartikowati, Sri; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of parents education level and motivation on student achievement. on Economic in MAN 2 Model Pekanbaru. Population in this study are students of class XI IPS in MAN 2 Model Pekanbaru with a total of 52 students. Research takes the entire population as a sample or is called a cencus study. Data collection is done through documentation and questionnaires. Data analysis using multiple regression analysis. The results of this study indicate (1) The level of parents education has a significant effect on learning achievement. With the tcount (4,139> t_tabel (2,010) or sig. And Sig. (0,000) <0,05. (2) Motivation to learn has a significant effect on the learning preset by value. Based on the results of regression analysis t count test (5,306)> t table ( 2,010) and Sig. (0,000) <0,05, with an R value of 0.599, this proves that the percentage of parents' level of education and learning motivation contribute 59.9% to learning achievement (Y) while the remaining 40.1 % is influenced by other variables not included in this regression model. from research results can be recommended, Students are expected to improve learning motivation, especially in terms of tenacity in carrying out tasks by frequently discussing or learning from the success of their friends.Keywords: Parents education level , Learning motivation, Learning achievement